2009
DOI: 10.1158/0008-5472.can-08-2750
|View full text |Cite
|
Sign up to set email alerts
|

Rat Umbilical Cord Stem Cells Completely Abolish Rat Mammary Carcinomas with No Evidence of Metastasis or Recurrence 100 Days Post–Tumor Cell Inoculation

Abstract: Genetically engineered stem cells efficiently deliver therapeutic proteins to cancer and other sites of inflammation. However, a major advantage would be realized if tumortrafficking stem cells that have not been genetically modified exhibit an inherent antitumor effect, thus circumventing the necessity of the expression of exogenous genes by the cells. We transplanted Fisher 344 rat-derived mammary adenocarcinoma cells (Mat B III) orthotopically into syngeneic F344 rats with an intact immune system. Rat umbil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 18 publications
13
118
0
1
Order By: Relevance
“…In this study, as a necessary preliminary step, they evaluated the effect of unengineered rat umbilical cord blood stem cells on Matt B III cancer cells in vitro and in vivo. To their surprise, the stem cells them-selves mediated a profound anti-tumor effect both in vivo and in vitro (17). In the present study, we demonstrate this anti-tumor effect in vivo and in vitro using human glioma cell lines and xenografts.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, as a necessary preliminary step, they evaluated the effect of unengineered rat umbilical cord blood stem cells on Matt B III cancer cells in vitro and in vivo. To their surprise, the stem cells them-selves mediated a profound anti-tumor effect both in vivo and in vitro (17). In the present study, we demonstrate this anti-tumor effect in vivo and in vitro using human glioma cell lines and xenografts.…”
Section: Introductionsupporting
confidence: 55%
“…As demonstrated, the authors used the co-culture method to obtain the effector/ target (E/T) cell ratios of 0:1, 1:1, 5:1, and 10:1 (16). A recent report has demonstrated that rat umbilical cord blood stem cells completely abolish rat mammary carcinomas with no evidence of metastasis or recurrence at 100 days post-tumor cell inoculation (17). In this study, as a necessary preliminary step, they evaluated the effect of unengineered rat umbilical cord blood stem cells on Matt B III cancer cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The G0/G1 arrest is evident in the decrease of CDK2 expression [50]. In vivo studies showed that both human and rat UCMSC treatment significantly decreased tumor weights [32,33,49,50]. In particular, intratumoral or systemic administration of rat UCMSC caused complete regression of orthotopic Mat B III grafts in the female F344 rat mammary gland to undetectable levels by 34 to 38 days (Fig.…”
Section: Tumoricidal Ability Of Ucmscmentioning
confidence: 90%
“…Further, injection of WJMSCs into immune-deficient mice did not produce teratomas [18]. The versatility and availability of umbilical cord stem cells make them a potent resource for transplant therapies for various diseases, including cancer [20].…”
Section: Treatment Of Hep-2 Cell Line With Wharton's Jelly Mesenchymamentioning
confidence: 99%
“…Ganta et al, [20] observed that rats with mammary carcinoma showed complete regression of the lesion with no evidence of metastases following intra-tumoral injection of rat umbilical cord matrix-derived stem cells. Similarly, intravenous injection of unengineered human MSCs in a xenotransplant rat model with induced human breast carcinoma led to a decrease in cancer burden as a result of the human MSCs homing to pulmonary metastases [24].…”
Section: Archives In Cancer Researchmentioning
confidence: 99%